1981
DOI: 10.1111/j.1749-6632.1981.tb29717.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Platelet Reactivity in Arthritis*

Abstract: We utilized a standardized in vitro method which employs transmission electron microscopy to monitor the degree of surface activation (cytoplasmic spreading) and amount of aggregation displayed by platelet populations from 314 patients with one of five distinct rheumatic diseases and from 72 normal subjects. The percentage of patients in each group whose platelet populations were hyperactive was as follows: polymyalgia rheumatica, 75 percent; scleroderma, 65 percent; primary gout, 61 percent; rheumatoid arthri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Further, platelet aggregates and platelet or PMP adherent to leukocytes have been detected in both blood and synovial fluids of RA patients [58,64,65,66,67,68,69,70]. In vitro, it was shown that platelets are hyper-responsive to further activation, potentially reflecting the in vivo priming of platelets during disease [71,72]. …”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Further, platelet aggregates and platelet or PMP adherent to leukocytes have been detected in both blood and synovial fluids of RA patients [58,64,65,66,67,68,69,70]. In vitro, it was shown that platelets are hyper-responsive to further activation, potentially reflecting the in vivo priming of platelets during disease [71,72]. …”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Examples are rheumatoid seropositivity, antibodies against beta-2-microglobulin and circulating immune complexes (another link between autoimmune reactions and prothrombotic state in RA) [53,56,57]. Interestingly, increased in vitro platelet sensitivity to agonists and autoimmune factors has also been found in other rheumatic diseases (e.g., polymyalgia rheumatica, systemic sclerosis, gout), where common mechanisms of immune complex formation and accelerated atherogenesis can be inhibited by anti-platelets [58].…”
Section: Measuring Platelet Aggregationmentioning
confidence: 96%
“…For that matter, several studies have shown elevated markers of thrombin generation and fibrin turnover, previously associated with augmented thrombotic coronary risk, in RA patients with active disease [81][82][83][84]. Moreover, findings of enhanced platelet reactivity and activation have been consistently reported, which evidently relates to and even predicts future adverse cardiovascular events [85][86][87][88][89].…”
Section: Coagulation Fibrinolysis and Platelet Functionmentioning
confidence: 98%